La prévention du crime par le développement social : une stratégie à la recherche d’une synthèse - Hastings, Ross (Criminologie, 1998)
This article addresses the potential of the notion of crime prevention through social developmnent (CPSD) to contribute to the creation and implementation of a comprehensive crime prevention strategy. CPSD shares the commitment to a proactive orientation, community participation and partnerships which are common to all versions of prevention. However, the concept incorporates different options.The article discusses three: the developmental version, with its focus on persistent delinquents; the social version with its concentration on rates of crime and victimization; and the communtiy version, with its concern with the problem of mobilization for action.The article concludes that a synthesis of these approaches is possible, but that this is not the equivalent of a comprehensive strategy; other elements must be included.